2023
DOI: 10.1097/pgp.0000000000000976
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Immunohistochemical Analysis of Mesonephric Marker Expression in Low-grade Endometrial Endometrioid Carcinoma

Yurimi Lee,
Sangjoon Choi,
Hyun-Soo Kim

Abstract: Immunohistochemical markers shown to be useful in identifying/confirming mesonephric/mesonephric-like differentiation (MLD markers) include thyroid transcription factor (TTF1), GATA-binding protein 3 (GATA3), and cluster of differentiation 10 (CD10). Only a few studies have examined the expression levels of MLD markers in endometrial endometrioid carcinomas (EECs). This study aimed to analyze the frequency and pattern of MLD marker expression in low-grade EECs. We performed immunostaining for the detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…It was found that 10.0% of tumors had at least moderate nuclear GATA3 staining. Considering that mesonephric-like adenocarcinoma is in the differential diagnosis of endometrioid carcinoma, the researchers concluded that pathologists should not exclude endometrioid carcinoma based solely on the presence of focal immunoreactivity for mesonephric markers (28).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that 10.0% of tumors had at least moderate nuclear GATA3 staining. Considering that mesonephric-like adenocarcinoma is in the differential diagnosis of endometrioid carcinoma, the researchers concluded that pathologists should not exclude endometrioid carcinoma based solely on the presence of focal immunoreactivity for mesonephric markers (28).…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining for Ki-67 was performed using whole-tissue sections as described previously [16][17][18][19][20][21][22][23][24]. For each case, the most representative slide containing >80% of viable tumor tissue was chosen for immunostaining.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%